Analysis of waiting time for elective surgical procedures in neurosurgery department at a tertiary care teaching hospital in NCT, India - Sardana, Sapna Ramani; Gupta, Shakti Kumar; Sharma, D. K.; Vij, Aarti; Kale, S. S. (International Journal of Research in Medical Sciences, 2017)
Background: Reported increases in waiting times for publicly-funded elective surgeries have intensified the need to decrease wait by healthcare providers and hence the study. Methods: Descriptive study done in neurosurgery department, to ascertain waiting times for its elective surgeries, included a retrospective analysis of admitted post-surgical patients and a prospective study using interviews with relevant stakeholders to do a process mapping. Results: Median time from decision of surgery to actual date of surgery was found to be 110.5 days. It was calculated that for optimum utilization of present available OTs, 19 extra beds are required and to address the existing load of patients waiting for their respective surgeries there is a need of 63 additional beds with 2 additional OTs functioning per day. Conclusions: The most common cause of waiting time was unavailability of vacant beds due to mismatch in demand-supply. The reason for postponement of surgery after admission was found to be lack of availability of theatre time followed by patient not being fit for surgery. Shortage of operating time was due to delayed start of operation theatre time. The study recommends improving admission process, restricting OPD time, standardized patient prioritization depending on relevant clinical criteria.